Stability and Compatibility of Antibiotics in Peritoneal Dialysis Solutions Applied to Automated Peritoneal Dialysis in the Pediatric Population. Issue 6 (November 2016) - Deslandes, Guillaume; Grégoire, Matthieu; Bouquié, Régis; Le Marec, Aude; Allard, Sophie; Dailly, Eric; Pineau, Alain; Allain-Launay, Emma; Jolliet, Pascale; Roussey, Gwenaëlle; Navas, Dominique
Objectives: Assess the stability of several antibiotics in peritoneal dialysis (PD) solutions under common conditions of use in pediatrics, particularly in automated PD. Methods: Amoxicillin, cefazolin, cefepime, ceftazidime, imipenem, cotrimoxazole, tobramycin, vancomycin, and the association of ceftazidime + vancomycin and ceftazidime + tobramycin, were tested in 3 different PD solutions: bicarbonate/lactate solution with 2 glucose concentrations (Physioneal 1.36 and 3.86%; Baxter Healthcare Corporation, Deerfield, IL, USA) and an icodextrin-containing solution (Extraneal; Baxter Healthcare Corporation, Deerfield, IL, USA). Concentrations were those recommended in guidelines for the treatment of peritonitis in pediatrics. Physioneal bags were incubated at 37°C for 24 hours, whereas Extraneal bags were stored 12 hours at room temperature (22 ± 2°C) and then 12 hours at 37°C. Drug concentrations were determined using high performance liquid chromatography (HPLC). Each measure was taken in triplicate. Stability of antibiotics was defined as less than 10% degradation of the drug over time. Results: Cefazolin, cotrimoxazole, tobramycin, and vancomycin were stable under studied conditions. Ceftazidime was stable 24 hours in icodextrin, 12 hours in Physioneal 1.36% and 6 hours in Physioneal 3.86%. The association of tobramycin or vancomycin did not influence the stability of ceftazidime. Cefepime and amoxicillin were stable 6 h, 4 h, and 8 h in Physioneal 1.36%, 3.86% and Extraneal, respectively. The stability of imipenem was very low: 2 h in Physioneal and 6 h in Extraneal. Moreover, an increasingly yellow coloration was observed with the use of imipenem, whereas no color change or precipitation occurred in other bags. Conclusion: Cefazolin, tobramycin, cotrimoxazole, and vancomycin are stable in PD solutions up to 24 hours and can be administered in the PD bag for the treatment of peritonitis, even in automated PD under studied conditions. However, amoxicillin, cefepime, ceftazidime, and imipenem must be used with caution due to their lack of stability.